GEOCHEMICAL BARRIERS: THEORY AND PRACTICAL APPLICATIONS - Perel'man A.I. (My University, 1986)
Geochemical barriers are zones in the Earth's crust with sharp physical or chemical gradients and they are often associated with concentrations of elements, sometimes to the extent of forming ore deposits. Four fundamental classes of geochemical barriers have been identified: (1) mechanical; (2) physico-chemical; (3) biochemical; (4) anthropogenic.Mechanical barriers are the simplest class and placer deposits are a good example. Physico-chemical barriers (the dominant class) are formed in zones characterized by sharp changes in the intensity of certain physico-chemical parameters of waters; tables of observed and predicted element associations have been prepared and these can be used to identify element concentrations which depend principally on the properties of waters. Biochemical barriers are specifically related to element concentrations brought about through reactions associated with life on Earth, for example, the accumulation of trace elements in effects are one variety. Although barriers consisting of combinations of several classes can occur, the main emphasis of this paper is on physico-chemical barriers with respect to ore deposits, soil geochemistry and groundwaters.